Diagnostic de L’état de dégradation des sols par salinisation de la plaine d’ELhmadna - BENTAMRA, ZOUBIDA (My University, 2017)
In view of the risk of soil degradation in the El Hmadna area due to salinization, the present study concerns a characterization of the physicochemical properties of a 4ha hectare plot. From soil samples taken from the studied site, measurements of infiltrometry are carried out using a membrane infiltrometer. The main findings indicate that: The soils are not saline but are alkaline and contain a limestone content with potassium dominance. The results show that the method of measuring infiltration under two matrix potential thresholds satisfactorily simulates the infiltration phenomenon under unsaturated conditions. In the unsaturated domain this method seems inadequate to account for the saturated hydraulic conductivity of the soil.
Keywords: salinization; infiltration; El Hmadena plain; soil physicochemical properties; salinisation; infiltration; plaine d’El Hmadena; propriétés physico-chimiques des sols; سهل شركة; تسلل; الملوحة; الخصائص الفيزيائية والكيميائية للتربة; Hmadena